Laparoscopic-endoscopic cooperative surgery for duodenal tumors: a unique procedure that helps ensure the safety of endoscopic submucosal dissection - Irino, Tomoyuki; Nunobe, Souya; Hiki, Naoki; Yamamoto, Yorimasa; Hirasawa, Toshiaki; Ohashi, Manabu; Fujisaki, Junko; Sano, Takeshi; Yamaguchi, Toshiharu (Endoscopy, 2015)
A new rendezvous-style surgical technique has been developed to ensure the safety of endoscopic submucosal dissection (ESD) for duodenal tumors. The new technique, called “laparoscopic-endoscopic cooperative surgery (LECS),” combines ESD with laparoscopic, reinforcing, seromuscular suturing. This case series report describes how three patients with a duodenal tumor were safely treated by LECS. ESD was performed by endoscopy, followed by closure of the mucosal defect using seromuscular suturing by laparoscopy. ESD was successfully completed in all patients. Endoscopic findings after suturing revealed that the mucosal defect was closed appropriately and tightly. None of the three patients experienced delayed perforation or stricture after LECS. LECS for extraction of duodenal tumors seems to be feasible and helps to ensure the safety of ESD in the duodenum.